Earth and atmosphere (Monmouthshire : AVP School Hill Centre, 2000)
A complete multimedia experience. This CD-ROM is part of a wide ranging and growing series of resources that covers large areas of the National Curriculum
System requirements: PC with 166MHz Intel Pentium processor, Windows 95, 98, NT, 16 MB of RAM (32MB is recommended), 1MB of display memory, 20MB of free hard disc space, 8X CD-ROM drive
Keywords: Earth; Atmosphere